2018
DOI: 10.1111/jcmm.13908
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Noxa by Bmi1 contributes to deguelin‐induced apoptosis in non‐small cell lung cancer cells

Abstract: Deguelin, a natural rotenoid isolated from several plants, has been reported to exert anti‐tumour effects in various cancers. However, the molecular mechanism of this regulation remains to be fully elucidated. Here, we found that deguelin inhibited the growth of non‐small cell lung cancer (NSCLC) cells both in vitro and in vivo by downregulation of Bmi1 expression. Our data showed that Bmi1 is highly expressed in human NSCLC tissues and cell lines. Knockdown of Bmi1 significantly suppressed NSCLC cell prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…MTS assays. MTS assay was performed as described previously (17). Briefly, human OSCC cells were seeded in 96-well plates at a concentration of 2×10 3 /well.…”
Section: Methodsmentioning
confidence: 99%
“…MTS assays. MTS assay was performed as described previously (17). Briefly, human OSCC cells were seeded in 96-well plates at a concentration of 2×10 3 /well.…”
Section: Methodsmentioning
confidence: 99%
“…Accumulating evidence reveals that the natural product deguelin exhibits profound anti-cancer potentials in multiple human cancer models, including lung cancer 14 , hepatocellular carcinoma 15 , colorectal cancer 16 , esophageal carcinoma 17 , metastatic melanoma 18 , and breast cancer 19 . The molecular mechanism studies showed that delay of cell cycle progression by inhibition of Aurora B kinase, regulation of metabolisms, such as suppression of glycolysis, down-regulation of angiogenesis and metastasis, and activation of intrinsic apoptosis were related to deguelin-mediated anti-tumor effect [20][21][22] . However, the effect of deguelin on EGFR signaling, as well as its inhibitory efficacy on both gefitinib sensitive and resistant cells, was not clear.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the small molecule through rational chemical design, natural products have more potential to be applied to tumor chemotherapy owing to their structural diversity. Recently, numerous natural compounds have been demonstrated exerting anti-tumor activity through the suppression of cell cycle progression, impairment of angiogenesis, induction of apoptosis, and inhibition of glycolysis [20,[29][30][31][32][33][34]. Piperlongumine is an amide alkaloid constituent of the Piper longum L. (long piper), which is also named as piplartine and used as an Ayurvedic medicine for a long time.…”
Section: Discussionmentioning
confidence: 99%